Mapping Out Commercial Gas Sensors to Measure Degradation Gases in Batteries - Al-Azzawi, Mohanad (My University, 2026)
This research presents a comprehensive literature review on the use and possibilities of commercial gas sensors to detect and monitor degradation in batteries. Battery cells, especially under aging or fault conditions, emit various gases due to internal chemical decomposition. These gases have potential to serve as a key indicator of battery health, performance, and safety. Detecting such emissions can help in identifying degradation and potential failures, ultimately contributing to improved battery management and lifespan estimation. The primary aim of this study is to evaluate gas sensor technologies capable of detecting emissions generated during battery degradation, including hydrogen, carbon monoxide, methane, and volatile organic compounds (VOCs). The focus is placed on sensors that can collect diagnostic information from within or near the battery cell, examining their operating principles, performance characteristics, and suitability for integration into battery monitoring, management, and control systems. The study particularly investigates electrochemical sensors, metal-oxide semiconductor (MOS) sensors, non-dispersive infrared (NDIR) sensors, and related technologies, assessing their capability to detect degradation-related gases and support early failure identification. The research methodology involves a comparative analysis of various gas sensor technologies through an extensive review of both recent and historical scientific literature. Key sensor parameters evaluated include sensitivity, selectivity, response time, long-term durability, and commercial availability. The review also examines how these sensors quantify and characterize gas emissions, which in turn reflect the extent and progression of battery decomposition and degradation. This analysis provides a foundation for identifying sensor technologies most suitable for advanced battery diagnostic and safety applications. Based on the literature review and comparative analysis, this study identifies several factors influencing sensor performance and reliability. It also outlines limitations that may lead to sensor failure or ineffective detection on critical gases. Through this evaluation, the thesis provides informed recommendations for selecting the most effective gas sensors suitable for integration into battery research, development and control. In conclusion, this study serves as a foundational reference for future experimental research, in using gas sensors as diagnostic tools for batteries particularly in addressing the state of health (SOH) of batteries. It also contributes to the advancement of sensor technology in the field of battery diagnostics and early fault detection.

Tämä tutkielma on kirjallisuuskatsaus kaupallisten kaasusensoreiden käytöstä akkujen heikkenemisen havaitsemiseksi ja seuraamiseksi. Akkujen kennot, erityisesti ikääntyessään tai vioittuessaan, aiheuttavat kaasupäästöjä, jotka johtuvat kennojen sisällä olevien materiaalien hajoamisesta. Nämä kaasut voivat toimia ensisijaisena osoituksena akun kunnosta, suorituskyvystä ja turvallisuudesta ja niiden havaitseminen auttaa tunnistamaan akkujen kunnon heikkenemistä ja mahdollisia vikoja, mikä mahdollistaa paremman akkujen hallinnan ja elinkaaren arvioinnin. Tämän tutkielman ensisijainen tavoite on arvioida kaasusensori teknologioita, joiden avulla pystytään havainnoimaan akkujen heikkenemisestä johtuvia kaasupäästöjä, mm. Hiilidioksidia, metaania ja haihtuvia orgaanisia yhdisteitä (VOC). Tutkielma keskittyy erityisesti akkukennoista tiedon keräämisen mahdollistaviin sensoreihin ja niiden toimintaperiaatteisiin, ominaisuuksiin sekä soveltuvuuteen osana akkujärjestelmiä. Tässä tutkielmassa tarkastellaan erityisesti sähkökemiallisia sensoreita, metallioksidisensoreita (MOS), epädispersiivisiä infrapuna sensoreita (NDIR), ja niihin liittyviä teknologioita ja arvioidaan sekä niiden kykyä havainnoida akkujen kuntoa. Tutkimusmenetelmänä käytetään vertailevaa analyysia, jonka avulla vertaillaan eri kaasusensori teknologioita tarkastelemalla sekä viimeaikaisia että aiempia tieteellisiä artikkeleita ja julkaisuja. Kaasusensoreiden keskeisimmät tarkasteltavat ominaisuudet ovat mm. sensorien herkkyys, selektiivisyys, aikavaste, kestävyys ja kaupallinen saatavuus. Tutkimus painottaa kaasusensoreiden soveltuvuutta havainnoida kaasuja riippuen kaasun määrästä ja laadusta, mikä heijastuu akun kunnon heikkenemiseen ja materiaalien hajoamiseen. Kirjallisuuskatsauksen ja vertailevan analyysin perusteella tämä tutkielma tunnistaa useita tekijöitä, jotka vaikuttavat sensoreiden suorituskykyyn ja luotettavuuteen. Lisäksi tutkielma tunnistaa rajoitteita, jotka voivat johtaa vikoihin sensoreissa tai kriittisten kaasujen tehottomaan tunnistukseen. Näiden arvioiden perusteella, tämä tutkielma esittää suosituksia tehokkaimmista sensoreista, jotka soveltuvat parhaiten käytettäviksi akkututkimuksessa. Tämä tutkielma tarjoaa pohjan tuleville kokeellisille tutkimuksille, kaasusensorien käytöstä akkudiagnostiikassa erityisesti liittyen akkujen kuntoon. Lisäksi tämä tutkielma edistää sensoriteknologian kehittämistä akkudiagnostiikan ja aikaisen vianmäärityksen osalta.
Keywords: Gas Evaluation in Batteries; Commercial Gas Sensors; Battery Management Systems BMS; Battery Degradation; Battery safety; Battery analytics